Axillary Lymph Nodes Hypermetabolism After BNT162b2 mRNA COVID-19 Vaccination in Cancer Patients Undergoing 18F-FDG PET/CT: A Cohort Study. (May 2021) - Bernstine, Hanna; Priss, Miriam; Anati, Tamer; Turko, Olga; Gorenberg, Miguel; Steinmetz, Adam Peter; Groshar, David
Abstract : Purpose: Recognition of the pattern of FDG uptake in hypermetabolic axillary lymph nodes (HALs) and association with recent messenger RNA (mRNA) vaccination are important to prevent patient anxiety and further needless examinations or costly biopsies in cancer patients. Materials and Methods: This study was a retrospective cohort study in a single tertiary care institution. We investigate the occurrence and pattern of HAL on FDG PET/CT scans from 650 consecutive cancer patients with recent BNT162b2 mRNA COVID-19 vaccination. Results: Between December 20, 2020, and February 8, 2021, 650 patients (351 female patients [54%]; mean age, 68.9 years) had recent mRNA COVID-19 vaccination and an FDG PET/CT scan. HALs were found in 57 (14.5%) of 394 patients (95% confidence interval [CI], 10.9%–18.7%) 12.3 ± 5.9 (1–22) days after dose 1 and in 111 (43.3%) of 256 patients (95% CI, 35.3%–52.2%; P < 0.0001) after 7.5 ± 5.4 (1–22) days after dose 2. There was no difference between dose 1 and dose 2 concerning SUVmax (3.7 ± 1.8 [1.3–11.3] and 4.5 ± 3.9 [1.4–26.3], P = 0.13, respectively), SUVmean (2.1 ± 1.0 [0.7–6.5] and 2.7 ± 2.4 [0.8–17], P = 0.08, respectively), and reactogenicity volume (2.7 ± 2.3 [0.2–11.6] cm 3 and 2.7 ± 2.4 [0.2–15.5] cm 3, P = 0.98, respectively). There was no difference in number and in size of positive lymph nodes between dose 1 and dose 2: 3.2 ± 2.2 (1–10) and 3.7 ± 2.4 (1–12) ( P = 0.18), and 1.4 ± 0.4 cm (0.7–2.5 cm) and 1.5 ± 0.4 cm (0.6–3.2 cm) ( P = 0.75), respectively. Conclusions: A cluster pattern of hypermetabolic ipsilateral small axillary lymph nodes is common after mRNA COVID-19 vaccination, mainly after the second injection.